Genome-Wide Profiling Reveals Alternative Polyadenylation of Innate Immune-Related mRNA in Patients With COVID-19 - An, Sanqi; Li, Yueqi; Lin, Yao; Chu, Jiemei; Su, Jinming; Chen, Qiuli; Wang, Hailong; Pan, Peijiang; Zheng, Ruili; Li, Jingyi; Jiang, Junjun; Ye, Li; et al. (Frontiers in Immunology, 2021)
The COVID-19 pandemic has caused many deaths worldwide. To date, the mechanism of viral immune escape remains unclear, which is a great obstacle to developing effective clinical treatment. RNA processing mechanisms, including alternative polyadenylation (APA) and alternative splicing (AS), are crucial in the regulation of most human genes in many types of infectious diseases. However, neither has been fully understood especially in SARS-CoV-2 infection. For the reason that the degree of 3′UTR variation in response to SARS-CoV-2 infection remains unknown, we performed de novo identification of dynamic APA sites using a public dataset of human peripheral blood mononuclear cell (PBMC) RNA-Seq data in COVID-19 patients. We found that genes with APA are enriched in immune-related categories such as pathogenic Escherichia coli infection, endocytosis, phagosome human cytomegalovirus infection, and Epstein-Barr virus infection signaling pathways. APA was also associated with immune-related gene expression in host cell. Additionally, expression of APA regulators was significantly upregulated in COVID-19 patients and the validation cohort. We also reported genome-wide AS events and enriched immune-related pathways upon SARS-CoV-2 infection. Interestingly, we found APA events may have stronger power to be biomarkers than AS in COVID-19 patients, suggesting that APA could act as a novel biomarker and potential therapeutic targets in those patients. Our study unprecedently reported annotation of genes with APA and AS in COVID-19 patients and highlighted the roles of APA’s variation in SARS-CoV-2 infection.